A Thai Junior High School Students 21st Century Information Literacy, Media Literacy, and ICT Literacy Skills Factor Analysis - Sangutai Moto; Thanin Ratanaolarn; Somkiat Tuntiwongwanich; Paitoon Pimdee (My University, 2018)
As Thailand moves through the 21st Century, the education system and resultant labour force must be prepared for the rapid changes in Thailand’s society, culture, politics, economy, and technologies. Previously, the 21st century framework has identified crucial elements to their future success as information literacy, media literacy, and information and communication technology (ICT) literacy skills. Given this priority, by use of multistage clustering sampling, 600 Thai junior high school students were selected, from which a five-level, 73-item Likert type agreement scale questionnaire was used to collect data from October 2017 to December 2017. The analysis of the student’s skills in information literacy, media literacy, and ICT literacy was conducted with the use of SPSS Version 24 and mean (¯(x )), standard deviation (S.D.), the Kaiser-Meyer-Olkin (KMO) test, and Bartlett's test of sphericity for analysis. Furthermore, a second-order confirmatory factor analysis was undertaken in which AMOS Version 24 software was used. Based on the second order CFA, it was found that the Information, Media and Technology Skills (IMTS) model was composed of three components that corresponded to the empirical data, with the most important element being ICT literacy, followed by media literacy, and finally, information literacy.
Keywords: Media Literacy; Technology-Enhanced Education Studies